Study on Near-Net Shape Forging of Large Marine Crank Throws - Longjiang Niu; Qingliang Zhang; Yongwan Zhang; Jingyu Wang; Weiping Luo; Donghang Liu; Tengfei Ma; Xavier Velay (Metals)
The crankshaft is a critical component in large marine ships, often regarded as the “heart” of the vessel due to its role in transmitting power and motion. This article addresses the technological challenges in the forging of marine crank throws, a key segment of the crankshaft. The study employed finite element simulations to evaluate three Near-Net-Shape (NNS) forming methods: One-Step Extrusion (OSE), Upsetting/Backward Extrusion (U/BE), and Grooving–upsetting/Backward Extrusion (G–U/BE). The results show that the G–U/BE method requires the lowest load. The grooving–upsetting step in the G–U/BE process forms a rigid journal end web shape that influences the subsequent backward extrusion, with the relative groove depth (the ratio of groove depth to width) playing a crucial role in the final forging quality. Optimal crank throw formation occurs when the ratio is 1.5; deeper grooves increase the load required, diminishing the effectiveness of the grooving–upsetting step. Scaled-down experiments validate G–U/BE as a practical and feasible method for producing large marine crank throw forgings, ensuring both the desired shape and microstructural properties.